Knowledge, Attitude and Awareness of Medical Students towards Medico-Legal Autopsy in Sangli, Maharashtra (Medico Legal Update, 2021)
For centuries, autopsy has been instrumental in establishing the cause of death both in clinical and forensiccases. Even though it helps in arriving at a decision regarding the cause of death and many other things, itsuse is declining recently, which should be a cause of concern. With this background, the present study hasbeen carried out in January 2020 on 150 medical students of 2nd year MBBS by using set of questionnaires,to assess their knowledge and attitude towards autopsy at department of Forensic Medicine and Toxicologyat BVDU & MC, Sangli, Maharashtra. This study shows the students had a reasonable knowledge and goodattitude towards medico-legal autopsy. Majority of the students agreed that need of autopsy in all unnatural,sudden, unexpected and suspicious death is mandatory and collection of viscera for histo-pathological andtoxicological analysis is useful. Majority of the students think that autopsy helps in solving crimes and givesinformation to police. Most of the study population shows interest in attending and performing a greaternumber of autopsies. Majority of the students agreed that post mortem examination is useful in medicaleducation. Majority of the study population says that autopsy is disrespect to human body. Most of the studypopulation is not aware of virtual autopsy